The effects of ethanolic extract of Phaleria macrocarpa (Scheff.) Boerl leaf on macrophage phagocytic activity in diabetic rat model - Ira Cinta Lestari; Muhammad Ghufron; Sri Herwiyanti; Yustina Andwi Ari Sumiwi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Diabetic patients suffer inflammation and immune deficiency as a consequence of the decrease in macrophage phagocytic activity, thus making them vulnerable to infection. The ability of Ethanolic Extract of Phaleria macrocarpa Leaf (EEPML) to increase macrophage phagocytic activity has also a potential in the diabetic case. EEPML also has anti-inflammatory effect. In this study the EEPML potential to increase peritoneal macrophage phagocytic activity and change M1 and M2 macrophage percentage in diabetic rat model is investigated. This was a quasi experimental study with post test only control group design. Fourty five male Sprague Dawley rats within the age of 8 weeks were classified into normal control group, diabetic control group with solvent, diabetic with 7mg/200g, 14mg/200g, and 28mg/200g of EEPML peroral administration, once a day. The diabetic rat model was made with streptozotocin and nicotinamide injection. The rats were terminated in 3rd, 14th and 25th day of extract administration. Peritoneal fluid was isolated then cultured for macrophage phagocytic activity assay with latex beads. M1 and M2 macrophage percentage was  analyzed using flow cytometry with anti CD40 and CD206 antibody. Result of statistical analysis show that  active macrophage and phagocytic index mean of EEPML rat groups on day 3, 14 and 25 was significantly higher than the control group. The mean of M1 macrophage percentage of EEPML rat groups was significantly higher than control on day 3 and 14, and lower on day 25, while mean of M2 macrophage percentage didn’t show any significant difference within groups. Conclusion of this study is administration of EEPML increases peritoneal macrophage phagocytic activity on day 3, 14 and 25. This is also increases M1 macrophage percentage on day 14, decrease M1 macrophage percentage on day 25, and doesn’t change peritoneal M2 macrophage percentage in diabetic rat model.